Bioactive Potential of Cicer arietinum L. Extracts Evaluated by Cytotoxicity, Larvicidal and Piscicidal Activity under Laboratory Conditions (Journal of Bio-Science, 2026)
Extracts of chickpea Cicer arietinum L. with petroleum ether (PE), CHCl3, and CH3OH were tested for cytotoxicity against brine shrimp Artemia salina L. nauplii, larvicidal activity against mosquito Culex quinquefasciatus Say larvae, and piscicidal activity against guppy Poecilia reticulata Peters. All chickpea extracts exhibited cytotoxicity, with the CHCl3 extract proving the most effective at a minimum LC50 of 7.27 ppm, followed by the CH3OH and PE extract, with LC50s of 22.05 and 27.33 ppm, respectively, after 48 h of exposure. Against mosquito larvae, the PE extract showed the highest larvicidal activity with an LC50 value of 38.59 ppm at 48 h, while the CH3OH and CHCl3 extracts gave LC50 values ​​of 66.01 and 72.22 ppm after 48 h of exposure. Against guppies, only the CHCl3 and CH3OH extracts of the tested plant showed favorable piscicidal activity. The CHCl3 extract proved more active, with an LC50 of 5.35 ppm, compared to 23.91 ppm for the CH3OH extract, after 48 h of exposure. The PE extract showed no lethality to the fish studied. Based on the intensity of sensitivity of the three test organisms to the chickpea extracts, the tested agents could be ranked in descending order of effectiveness as follows: P. reticulata (CHCl3; LC50 = 5.35 ppm) > A. salina nauplii (CHCl3; LC50 = 7.27 ppm) > C. quinquefasciatus larvae (PE; LC50 = 38.59 ppm).J. Bio-Sci. 33(2): 57-66, 2025